69.9k views
1 vote
Solve this system by substitution. y = 6x - 17 y = -4x+3

Solve this system by substitution. y = 6x - 17 y = -4x+3-example-1

1 Answer

4 votes

\begin{gathered} y=6x-17\ldots..eqn\text{ (i)} \\ y=-4x+3\ldots..eqn(ii) \\ \text{Equating Eqn (i) and Eqn(i}i),\text{ we have,} \\ 6x-17=-4x+3^{} \\ 6x+4x=3+17 \\ 10x=20 \\ x=(20)/(10) \\ x=2 \end{gathered}

substituting 2 for x in eqn (i), we have,


\begin{gathered} y=6(2)-17 \\ y=12-17 \\ y=-5 \end{gathered}

Therefore, x=2 and y= - 5

User Meirion
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.